Industrial reform in China: the case of the alcohol industry - Zhai, Changlin (2014)
Chinese alcohol industry is a main contributor of China’s GDP, and it was led by some domestic large alcohol organisations. However, since China became as a member of World Trade Organisation in 2001, foreign beverage alcohol products entered into Chinese market rapidly. Entertainment places being as a large demand part, most of the market shares in this part are occupied by foreign alcohol products. Except for the threat from foreign competitors, domestic alcohol organisations still are facing some challenges, such as operation problems, technology problems and chaotic market order. Consequently, the reform is necessary to be launched and accelerated, otherwise the China’s alcohol industry would be crashed easily, and the national economy would be shocked significantly.